A Small Space for Playful Messaging in the Workplace: Designing and Deploying Picco - Downs, John; Villar, Nicolas; Scott, James; Lindley, Siân; Helmes, John; Smyth, Gavin (Proceedings of the 2014 ACM conference on Designing Interactive Systems, 2014)
We present Picco, a tiny situated display for drawings and simple animations, which are created on a dedicated tablet app. Picco was designed to support playful messaging in the workplace through a glanceable desktop device that would place minimal demands on users. Two studies of the device at work demonstrated how crafting was an expression of intimacy when the device was used to connect the workplace to the home, and a way of demonstrating skill and humor to a broad audience when messages were sent amongst co-workers. However, the level of skill needed to produce these messages became a barrier to entry for some co-workers. Our findings suggest that visible ownership of a situated device, which can be personalized in other ways, can underpin a secondary level of participation that is crucial in supporting a sense of involvement when the level of crafting required can stifle more direct participation.